2016
DOI: 10.1212/wnl.0000000000003250
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve in frontotemporal degeneration

Abstract: Objective: To evaluate if cognitive reserve (CR) contributes to interindividual differences in frontal gray matter density (GMD) and executive impairment that underlie heterogeneity in the disease course of confirmed frontotemporal lobar degeneration (FTLD) pathology.Methods: Fifty-five patients with autopsy confirmation or a pathogenic mutation consistent with underlying tau (FTLD-tau) or TDP-43 (FTLD-TDP) pathology and 90 demographically comparable healthy controls were assessed with T1 MRI and neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Lobe-wise analysis did not reveal differences between pGRN+ and yCTL, but the subtle, focal nature of disease onset revealed itself upon voxel-wise investigation. While our work shows progressive changes in both GM and WM in pGRN+ individuals, our findings may be confounded in part by mechanisms such as cognitive reserve ( Massimo et al, 2015 ; Placek et al, 2016 ; Premi et al, 2013 ) that assist these individuals in maintaining their apparent presymptomatic status despite observed anatomic alterations. The sample size for our longitudinal evaluation of this rare mutation is small.…”
Section: Discussionmentioning
confidence: 62%
“…Lobe-wise analysis did not reveal differences between pGRN+ and yCTL, but the subtle, focal nature of disease onset revealed itself upon voxel-wise investigation. While our work shows progressive changes in both GM and WM in pGRN+ individuals, our findings may be confounded in part by mechanisms such as cognitive reserve ( Massimo et al, 2015 ; Placek et al, 2016 ; Premi et al, 2013 ) that assist these individuals in maintaining their apparent presymptomatic status despite observed anatomic alterations. The sample size for our longitudinal evaluation of this rare mutation is small.…”
Section: Discussionmentioning
confidence: 62%
“…Neuroimaging studies also showed that CR contributes to inter-individual differences in frontal gray matter density. Higher gray matter density in the frontal regions is associated with higher CR and executive function (Placek et al, 2016). In the current study, moderator analyses revealed that education levels and occupation complexity may be a more sensitive proxy for CR in the present sample.…”
Section: Discussionmentioning
confidence: 41%
“…On the other hand, APOEε2 genotype in interaction with higher CR plays a protective role for cognitive functioning (Pettigrew et al, 2013). Similar links between genotype, CR and progressing symptoms of dementia (Placek et al, 2016) were reported in genetically determined (20-50 % of FTD cases) familial frontotemporal dementia (fFTD) (Olszewska, Lonergan, Fallon, & Lynch, 2016).…”
Section: Introductionmentioning
confidence: 64%